PEMBAYARAN PAJAK DALAM PERSPEKTIF SYARIAH DITINJAU DARI MAQASHID SYARIAH - Oveliana Puspitasari; Fauzatul Laily Nisa (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to explore information regarding the meaning of tax based on maqashid Syariah using a literature study research method involving the process of collecting relevant data related to research topics from various sources, academic books, scientific articles, research reports, and theses. The results of this research explain that from a sharia perspective, paying taxes is not only a legal obligation, but also a moral and social responsibility that supports general welfare (maslahah ammah). If managed well and transparently, taxes can be an effective tool for achieving the goals of maqashid sharia and creating a just and prosperous society.